Effect of pressure and temperature on the white light produed by Ytterbium (III) doped and undoped Yttrium Silicate nanopowders excited by a laser diode - ERDEM, MURAT (ELSEVIER SCIENCE BV, 2017)
In the present study, we have directed our attention to yttrium silicate nanopowders undoped and with different ytterbium (III) dopant concentrations, systems that, when illuminated by a laser diode emit white light. We have investigated the effects that two physical parameters, pressure of the ambient and temperature of the powders have on the emission of the white light. We have observed that low pressure and high temperatures enhance the intensity of the emitted white light. At high pressure, the output from the nanopowder is represented by groups of sharp lines due to ytterbium cooperative emission and unwanted erbium impurities. As the pressure decreases to 0.01 mbar, the spectrum changes to a wide band resembling the white light spectrum. High temperatures of the nanopowders enhance the emission of white light. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Pressure effect; Temperature effect; White light; Ytterbium (III); Yttrium silicate; Sol-gel; SOL-GEL METHOD; UP-CONVERSION; LUMINESCENCE PROPERTIES; POWDERS; NANOPHOSPHORS; GENERATION; EMISSION; CRYSTALS; ER3+